The detection problem: an eight-decade challenge: the difficulty of practically detecting and discriminating mines, booby traps, and victim operated improvised explosive devices - Evans, Roly H. P.; Temple, Tracey; Nelson, Liz (The Center for International Stabilization and Recovery (CISR) : James Madison University, 2024)
Reliably detecting and discriminating mines, booby traps, and victim operated improvised explosive devices remains a stubborn problem for both humanitarian demining organizations and the military. Since mines were widely used during the Second World War, much effort has been expended on the detection problem, with limited success. The aim of being able to positively identify a device first time remains elusive since the scientific challenge of positively identifying different substances in the ground is formidable. This article critically examines the detection problem and suggests that in the continued absence of a ‘silver bullet’ technological solution, the best means currently available to manage the risk of concealed explosive devices is the systematic collection and analysis of relevant operational data from the field.
© The Authors